2020
DOI: 10.1007/978-3-030-64148-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Consistency in GSD: Social Factors, Structures and Interactions

Abstract: Global software development (GSD) implies a distributed development organization, where coordination is needed to efficiently achieve development objectives. So far, socio-technical congruence has examined coordination needs and activities through software code dependencies. However, GSD requires coordination beyond software artifacts. In this paper, we present an interview-based study of software practitioners from companies engaged in GSD. The study examines how different dimensions of interactions are inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The increasing globalization of the software industry with different stakeholders and infrastructures has drawn attention to GSE. Researchers and practitioners [3] presented methods and processes [4,5], focusing on coordination [6,7], tools to enhance collaboration [8,9], strategies to support a GSE-based business model to hire distributed teams [10,11], and pedagogies for GSE curricula [12,13] to improve project management in a distributed environment. While the research in GSE is progressively growing [14] and provides support for diverse challenges [15], researchers highlighted the limited literature available to support and manage software design activities in distributed teams [16].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing globalization of the software industry with different stakeholders and infrastructures has drawn attention to GSE. Researchers and practitioners [3] presented methods and processes [4,5], focusing on coordination [6,7], tools to enhance collaboration [8,9], strategies to support a GSE-based business model to hire distributed teams [10,11], and pedagogies for GSE curricula [12,13] to improve project management in a distributed environment. While the research in GSE is progressively growing [14] and provides support for diverse challenges [15], researchers highlighted the limited literature available to support and manage software design activities in distributed teams [16].…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, they developed a model to deal with coordination issues of a vendor organization in GSD. Sievi-Korte et al [37] adopted the interview method in the different practitioners of GSD companies and concluded that how various aspects of interaction are interlinked? And how social factors and structures are affected in software development?…”
Section: Literature Reviewmentioning
confidence: 99%
“…To a large degree, existing studies focus on understanding how the software is composed, and how developers work together. This has resulted in concepts discussing this relation such as socio-technical congruence [17], and expanding them to other interaction between individuals, organization and processes [11]. A dimension that has received less attention is the fact that participants FLOSS communities have different backgrounds, and that participating developers can also be characterized by factors other than their direct contributions.…”
Section: Introductionmentioning
confidence: 99%